Analyzing Online Public Sentiment Toward Corporate Crisis in the Age of Big Data and Automation - Aqida Nuril Salma (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
The emergence of social media has created a new environment for digital communities to share their opinions and thoughts. Particularly in times of crisis where online platforms such as Facebook and Twitter have become the first destination for people to express their thoughts and share crucial information. On the other hand, social media and its algorithms have created very large amounts of data to enable Public Relations practitioners to access the data through data mining techniques. As such, this study aims to analyze online public sentiment toward a corporate crisis using big data and automation. Unlike research in the fields of information systems and computer science, which focuses on building methodology and tools, this study demonstrates the possibilities of basic big data utilization as well as linking the findings to the foundations of social theory and public relations crisis. To reach its aims, Twitter data has been collected, analyzed and visualized to perform a text mining and sentiment analysis for analyzing public sentiment about Garuda Indonesia crisis in 2019. Drawing on current literature on public relations and crisis management in digital world, the finding suggests the need of having big data skills for public relations practitioners if they wish to survive in a fully digitized society. Finally, I expect that this project will be important to draw in new discussion for scholars in a variety of area studies, such as strategic communication, corporate communication, digital public relations and even data science.